2018
DOI: 10.3126/jonmc.v7i1.20842
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Vaginal Birth After Caesarean (VBAC): Sharing Experience From a Tertiary Care Center of Eastern Nepal

Abstract: Background: Rising rates of cesarean section is a matter of great concern and trial of labor in previous cesarean section women is an attractive alternative. Vaginal Birth After Caesarean (VBAC) may be one of the strategy developed to control the rising rate of cesarean deliveries in our country. Analyzing outcome of previous caesarean pregnancies will provide an insight for reducing the caesarean rates and formulating protocols and policies for trial of labor. The purpose of this study is to evaluate the preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Despite the fact that the two studies used the same study designs, the differences in the study findings might be attributed to differences in the study participants as well as differences in the geographical regions where the two investigations were done. The current findings differ from the findings of a prospective cross-sectional study at an Eastern Nepal Tertiary Care Center, which revealed that there were three cases of bladder injury as well as wound infection, which was more commonly found in failed VBAC cases, and among them, six had hemoglobin levels of 8 gm%, requiring blood transfusion postoperatively, but none of the patients had significant blood loss intraoperatively [20]. Although both studies were conducted in tertiary care hospitals, the disparity in study outcomes could be attributed to differences in the degrees of expertise of health workers as well as differences in the availability of sophisticated obstetrics equipment in the two study centers.…”
Section: The Outcomes Among Women Who Underwent Trial Of Labor After ...contrasting
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the two studies used the same study designs, the differences in the study findings might be attributed to differences in the study participants as well as differences in the geographical regions where the two investigations were done. The current findings differ from the findings of a prospective cross-sectional study at an Eastern Nepal Tertiary Care Center, which revealed that there were three cases of bladder injury as well as wound infection, which was more commonly found in failed VBAC cases, and among them, six had hemoglobin levels of 8 gm%, requiring blood transfusion postoperatively, but none of the patients had significant blood loss intraoperatively [20]. Although both studies were conducted in tertiary care hospitals, the disparity in study outcomes could be attributed to differences in the degrees of expertise of health workers as well as differences in the availability of sophisticated obstetrics equipment in the two study centers.…”
Section: The Outcomes Among Women Who Underwent Trial Of Labor After ...contrasting
confidence: 99%
“…That study found that the adjusted RR for severe maternal morbidity and mortality was 1.96 (95% CI 1.76 to 2.19) for uterine rupture and 6.41 (95% CI 4.84 to 8.50) for other complications. The current study's findings contradict those of a prospective cross-sectional study conducted at an eastern Nepalese tertiary care center on a trial of vaginal birth after caesarean (VBAC), which found that among 8 cases of scar tenderness, none of the patients ruptured intra-operatively [20] indicating that scar tenderness may not be a reliable indicator of impending or complete uterine rupture. Despite the fact that three women were suspected of having uterine ruptures before surgery, none of them burst intraoperatively.…”
Section: The Outcomes Among Women Who Underwent Trial Of Labor After ...contrasting
confidence: 99%